Nomogram for prediction of plastic bronchitis in Chinese children with pneumonia - Fang, Xiaoqian; Lu, Hemin (Frontiers in Pediatrics, 2025)
BackgroundThis study investigated risk factors for plastic bronchitis (PB) in children with pneumonia and created a nomogram for early detection.MethodsWe retrospectively analyzed data from 487 children with pneumonia who underwent bronchoscopic alveolar lavage between 2018 and 2024. Children were divided into a PB group (n = 65) and a No-PB group (n = 422). Key indicators were identified using regression analysis, and a nomogram prediction model was developed. Its effectiveness was evaluated using receiver operating characteristic (ROC) curves, calibration curves, decision curve analysis (DCA), and the bootstrap (BS) method.ResultsA total of 65 patients (13.3%) out of 487 had PB. Multivariate logistic regression analysis indicated that mycoplasma infection, atelectasis, high fever peak, high neutrophil levels and elevated lactate dehydrogenase levels were risk factors for PB development. Additionally, the BS-ROC curve of the developed nomogram had an area under the curve value of 0.857 (95% confidence interval: 0.808–0.905). The calibration curve analysis revealed a strong agreement between the actual and predicted probabilities of PB development, and DCA highlighted the clinical relevance of the nomogram.ConclusionsA nomogram for MP infection, fever peak, LDH, maximum neutrophils percentage (N%max), and atelectasis was established to predict the risk of PB in children with pneumonia. The nomogram effectively identifies PB early, and bronchoscopy is advised for high-risk children. However, the nomogram needs external validation before practical use.